Análise da competitividade brasileira no mercado de internacional de limão e lima ácida - Monteiro, Tiago Barros (Brasil, 2024)
The present study aims to investigate how Brazil's competitiveness developed in the global lemon market from 2002 to 2022. For this, a comprehensive analysis of Brazilian competitiveness in this market is conducted, considering the Revealed Comparative Advantage indices (RCA), Relative Market Position (RPM), and coverage rate, as well as investigating the sources of export growth through the Constant Market Share model. The hypothesis raised is that Brazil has evolved competitively in the international lemon market. The results obtained reveal that, over the analyzed period, Brazil demonstrated competitiveness, with a trend of growth in RCA and RMP indicators. The Constant Market Share model indicates that most of the competitiveness gains occurred in the first half of the studied period, while in the second half, although there were competitiveness gains, export growth was mainly driven by the increase in global exports.